High cycle fatigue behaviour of impact treated welds under variable amplitude loading conditions. (December 2015) - Ghahremani, Kasra; Walbridge, Scott; Topper, Tim
Highlights: Variable amplitude (VA) fatigue tests were conducted on two different welded joints. Effects of load cycles with high stress ratios and large tensile overloads were studied. A number of previously proposed recommendations for the fatigue design of impact treated welds are evaluated. The nominal, structural, and effective notch stress approaches were considered. Characteristic S–N curves are proposed for the fatigue design of treated welds under VA loading in the high cycle domain. Abstract: A comprehensive variable amplitude (VA) fatigue testing program and analysis was performed to address a number of concerns raised regarding the use of impact treatments for the fatigue enhancement of welds in the high and ultra-high cycle (up to 100 million cycles) domains. A total of 67 fatigue tests were conducted on two different welded joints representing load-carrying and non-load carrying welds in steel structures. Two different VA loading spectrums, generated using traffic data and influence lines for highway bridge girders, were used. The effects of load cycles with high stress ratios ( R > 0.4) and large tensile overloads (greater than the yield strength) were studied. The test results were then used to evaluate a number of previously proposed recommendations for the fatigue design of impact treated welds. The nominal, structural, and effective notch stress approaches were considered. Finite element (FE) analysis was performed to determine the structural and effective notch stresses. A statistical analysis of the fatigue test results was conducted and characteristic S – N curves with slope, m = 5 are proposed for the fatigue design of treated welds under VA loading in the high cycle domain.